Pendampingan Penggunaan Aplikasi Publish Or Perish dan Zotero dalam Penyusunan Buku Ajar Kurikulum Merdeka pada Majelis Guru Pondok Pesantren Royatul Islam - Ratmiati, Ratmiati; Fathia, Wilda; Marwan, Syaiful; Muspardi, Muspardi; Yusmanila, Yusmanila (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Having the ability to compile textbooks that can be used in learning is certainly one of the factors that can support a teacher's professionalism. However, to be able to write well you need continuous practice and knowing writing tools, one of which is a tool that can add references and bibliography. Therefore, applications are needed that can help teachers add references and bibliography, namely Publish or Perish (PoP) and Zotero. This research aims to describe the use of the PoP and Zotero digital applications in the process of preparing textbooks by the board of teachers at the Royatul Islam Islamic Boarding School, consisting of twenty teachers. The methods applied in this activity are lecture, demonstration and simulation methods. The flow of implementing this research is divided into three stages, namely the preparation stage, implementation stage, and evaluation stage. The data analysis technique uses descriptive analysis techniques. The research results showed that 90% of participants answered that they were able to operate the PoP digital application to find references in compiling textbooks. Apart from that, 90% of training participants in using this digital platform agreed that the PoP and Zotero applications would increase their knowledge and skills in searching for references and bibliography in compiling textbooks